2011
DOI: 10.1055/s-0031-1275494
|View full text |Cite
|
Sign up to set email alerts
|

The Profunda Femoris Artery “Fourth Perforator” Island Flap: A New Perforator Flap in Lower-Limb Reconstruction

Abstract: Although the lateral thigh flap has been well described as a fasciocutaneous flap based on one or more of the four perforators of the profunda femoris artery, the role for these individual perforators as perforator flaps has not been described. These profunda femoris artery perforators offer a particularly useful option in lower-limb reconstruction. In fact, a perforator flap based on the profunda femoris artery fourth perforator (PFA-P4) has not been described to our knowledge. We describe the utility of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although this study does not preclude the use of local flap options, and certainly we have had success with such options, 27,28 where a free flap is indicated, the current study highlights that unlike widespread past opinion, FC flaps may in fact lead to improved outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…Although this study does not preclude the use of local flap options, and certainly we have had success with such options, 27,28 where a free flap is indicated, the current study highlights that unlike widespread past opinion, FC flaps may in fact lead to improved outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…The perforating branches of the profunda femoris artery have numerous clinical implications. Examples include providing an important collateral circulation in atherosclerotic disease, being in danger of iatrogenic injury in surgical fixation of femoral fractures and providing a basis for reconstructive surgery and embolisation.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two studies have reported knee joint reconstruction using this flap; one study included seven patients with soft tissue defects measuring 100–150 cm 2 around the knee joint 5 , and the other described a single patient who underwent the reconstruction of a soft tissue defect measuring 8 × 6 cm on the lateral aspect of the knee joint. 6 …”
Section: Discussionmentioning
confidence: 99%